Analisis Yuridis Tindak Pidana Penipuan Atas Tipu Muslihat Terhadap Pekerja Seks Komersial Berdasarkan Pasala 378 Kuhp Tentang Tindak Pidana Penipuan - Rania Chaerunnisa; Aryo Fadlian (Jurnal Ilmiah Wahana Pendidikan, 2022)
This crime, regulated under Article 378 of the Criminal Code, is primarily known as fraud and is commonly referred to as “opriching.” Article 378 of the Criminal Code states: "Anyone with the intention of unlawfully benefiting himself or another person, by using a false name or false dignity, by deceit, or a series of lies, moves another person to hand over something to him, or to give him a debt. or write off a debt is punishable by fraud with a maximum imprisonment of four years. "Any hand that gives something to him, thereby paying off a debt or canceling a claim is punishable by a prison sentence of up to four years." It has both subjective and objective elements. This research uses a normative juridical approach. Normative jurisprudence is the study of the legal basis, legal system, level of legal agreement, and comparative law. This normative juridical is an attempt to take an inventory of positive law. In this approach, prescriptive rules are used to explore legal issues of compliance with social life. The act of cheating is an act of lying accompanied by a series of other lies that are not true, people who commit fraud usually do it for their own benefit to achieve a goal. The act of cheating is a word, an action that is planned and makes it seem like it is true or not. Commercial Sex Work (CSW) is a job by doing sexual acts with a reward from the person who buys the sexual service.